IBN Rasha's Rational Approach to the Problems of Existence (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article deals with the philosophical teachings of Ibn Rushd , repeating that the enlightenment teachings of the scholar were put forward in the context of the medieval religious fanaticism.